Perlindungan Hukum Hak Pekerja Atas Upah Pada Perusahaan Pailit Pasca Putusan Mahkamah Konstitusi Nomor 67/PUU-XI/2013 - Fachrurahman, Indra; Anggraeni, Happy Yulia; Wahyuni, Fitri (Pemuliaan Hukum, 2021)
In principle, all wages in arrears must be paid after the assets of the bankrupt Debtor are sold and the distribution list has been determined by the Court based on the curator's proposal. Meanwhile, based on the Constitutional Court Decision No. 67/PUU-XI/2013, the Constitutional Court has explicitly provided protection for workers' rights by providing legal certainty to prioritize workers' rights so that they can obtain their own rights in the event the company concerned goes into bankruptcy. The position of other rights of workers or laborers with the Constitutional Court Decision Number 67/PUU-XI/2013 takes precedence over claims for state rights, auction offices, and public bodies established by the Government. But the status of other rights of workers or laborers is still under the bill of wage rights and separatist creditors. So in practice, if a company is declared bankrupt, then the other rights of workers or workers are in third position after the settlement of wage rights and claims of separatist creditors. The Bankruptcy Law is revised or amended again, so that the rights of each creditor that have been regulated in other laws do not overlap, so that its implementation is not too difficult in reality.Pada prinsipnya semua upah buruh yang tertunggak wajib dibayarkan setelah aset Debitur yang pailit dijual dan daftar Pembagian sudah ditetapkan oleh Pengadilan berdasarkan atas usulan kurator. Sedangkan berdasarkan Putusan MK No. 67/PUU-XI/2013, MK telah secara tegas memberikan perlindungan terhadap hak pekerja dengan memberikan kepastian hukum untuk memprioritaskan hak pekerja agar dapat memperoleh haknya sendiri dalam hal perusahaan yang bersangkutan mengalami kepailitan. Kedudukan hak-hak lain pekerja atau buruh dengan adanya Putusan Mahkamah Konstitusi Nomor 67/PUU-XI/2013 didahulukan atas tagihan hak negara, kantor lelang, dan badan umum yang dibentuk Pemerintah. Tetapi kedudukan hak-hak lain pekerja atau buruh masih berada di bawah tagihan hak upah dan kreditur separatis. Sehingga pada praktiknya apabila suatu perusahaan diputuskan pailit, maka hak-hak lain pekerja atau buruh berada di posisi ketiga setelah pelunasan hak upah dan tagihan kreditur separatis. Undang-Undang Kepailitan diperbaiki ataudiubah lagi, agar hak-hak setiap kreditor yang telah diatur dalam perundang-undangan lainnya tidak tumpang tindih, sehingga penerapan dalam kenyataannya tidak terlalu sulit.